2023
DOI: 10.1037/sgd0000641
|View full text |Cite
|
Sign up to set email alerts
|

The role of internalized transphobia and negative expectations in the relationship between identity-specific intimate partner violence and mental health outcomes in transgender and gender nonconforming young adults.

Abstract: Transgender and gender nonconforming (TGNC) individuals are at increased risk for mental health problems, including depression, anxiety, and posttraumatic stress disorder (PTSD). The Gender Minority Stress Model posits that this disparity can be explained by several pathways, with proximal stressors (e.g., internalized transphobia, negative expectations) mediating the relationship between distal stressors (e.g., intimate partner violence [IPV]) and mental health. The current study sought to assess one such pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
(160 reference statements)
0
4
0
Order By: Relevance
“…The current review aims to adopt an intersectional lens to explore the mental and physical health consequences of IPV victimization among SGM individuals, and to synthesize the existing 2020), and queer/pansexual/asexual/demisexual/other non-heterosexual orientation (Beymer et IPV victimization was signi cantly associated with PTSD in ve studies. For instance, Taber et al (2023) found that experiencing either form of identityspeci c IPV was associated with a signi cantly higher score on the Posttraumatic Stress Disorder Checklist (PCL-6) (Han et al, 2016) (p < .001) and that 1) the total and direct relationship of transgender-related IPV with PTSD and 2) the total and direct relationship between identity abuse with PTSD were signi cant based on 95% CI. In addition, Stults et al (2015) found that in a sample of Young Men Who Have Sex with Men, lifetime IPV victimization was signi cantly correlated with PTSD symptoms (r = .23, p < .001).…”
Section: Violence Exposure Among Sexual and Gender Minoritiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The current review aims to adopt an intersectional lens to explore the mental and physical health consequences of IPV victimization among SGM individuals, and to synthesize the existing 2020), and queer/pansexual/asexual/demisexual/other non-heterosexual orientation (Beymer et IPV victimization was signi cantly associated with PTSD in ve studies. For instance, Taber et al (2023) found that experiencing either form of identityspeci c IPV was associated with a signi cantly higher score on the Posttraumatic Stress Disorder Checklist (PCL-6) (Han et al, 2016) (p < .001) and that 1) the total and direct relationship of transgender-related IPV with PTSD and 2) the total and direct relationship between identity abuse with PTSD were signi cant based on 95% CI. In addition, Stults et al (2015) found that in a sample of Young Men Who Have Sex with Men, lifetime IPV victimization was signi cantly correlated with PTSD symptoms (r = .23, p < .001).…”
Section: Violence Exposure Among Sexual and Gender Minoritiesmentioning
confidence: 99%
“…IPV victimization was signi cantly associated with depression in twelve studies. Taber et al (2023) found that experiencing either form of identity-speci c IPV was signi cantly associated with higher scores on the PHQ-9 measure (PHQ-9)(Kroenke et al, 2001) (p < .001). In addition, the authors found that the total and direct relationships between transgender-related IPV and depression and between identity abuse and depression were signi cant based on 95% CI (Taber et al 2023).…”
Section: Depressionmentioning
confidence: 99%
See 2 more Smart Citations